Cherry blossoms after winter 3 - Bamwoo (Bamwoo. Cherry blossoms after winter, 2025)
"As they graduate from high school and prepare for university, Haebom and Taesung have not only rekindled their friendship-they're officially a couple! Haebom is blissfully happy, but he also feels more pressure than ever. He and Taesung still have to hide their relationship, and Haebom is determined to do well in school and repay Taesung's mother for her generosity. Taesung secures a place for them to live together, and they start their freshman year of college, where Haebom finds himself distracted by all the girls drawn to Taesung. Little does Haebom know that someone sinister has their eyes on him, too. As they navigate a whirlwind of unexpected events and complicated emotions, can Haebom and Taesung weather the storm of this new chapter in their relationship?"